Adaptasi Permainan Cangkul Lidi Berbasis Digital Melalui Pendekatan Atumics Sebagai Wujud Pelestarian Budaya Generasi Milenial - Nida Putri Israni; Siti Rahayu; Zuleha Zuleha; Novang Cahya Sri Kartini (Journal of Creative Student Research, 2024)
The aim of this research is to adapt the hoe stick game into a digital based game as an effort to preserve it by developing the original traditional hoe stick game without losing the cultural essence contained in it. The method used in this research uses a qualitative descriptive approach using literature study with the aim of finding several journal articles. The results of this research are adaptations that use the ATUMICS approach where there are two levels, namely the micro and macro levels. Where at the micro level it refers to the six basic elements, namely Artefack, Technique, Utility, Material, Icon, Concept, and Shape. Meanwhile, the macro level is more about enthusiasm and motivation for the products produced.